Integrasi Integrasi Nilai-Nilai Hadis Tarbawi ke dalam Teori Konstruktivisme untuk Mewujudkan Pendidikan Holistik di Era Modern - Zamhariroh, Nazila Mumtaza; Kurjum, Mohammad (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2024)
Modern education faces significant challenges in developing individuals who are not only cognitively intelligent but also possess strong character and balanced emotional and social skills. One approach to strengthening holistic education is by integrating the values of hadith tarbawi into constructivist theory, which emphasizes active and participatory learning. This study aims to explore the relevance and application of integrating hadith tarbawi values into constructivist theory to achieve balanced holistic education in the modern era. The research method used is a literature review with content analysis of relevant sources on constructivist theory and hadith tarbawi. The main findings reveal that integrating hadith tarbawi values, such as morality, discipline, and responsibility, can enrich the constructivist approach, which focuses on active learning experiences and knowledge construction. These values also strengthen the development of students’ character, support a balance between cognitive and moral aspects, and contribute to creating more holistic education. The conclusion of this study indicates that the combination of hadith tarbawi values and constructivist theory has the potential to provide a more comprehensive and balanced educational approach, which is essential in addressing the challenges of education in the modern era.